Axonal Organelles as Molecular Platforms for Axon Growth and Regeneration after Injury - Petrova, Veselina; Nieuwenhuis, Bart; Fawcett, James W; Eva, Richard (International journal of molecular sciences, 2021)
Investigating the molecular mechanisms governing developmental axon growth has been a useful approach for identifying new strategies for boosting axon regeneration after injury, with the goal of treating debilitating conditions such as spinal cord injury and vision loss. The picture emerging is that various axonal organelles are important centers for organizing the molecular mechanisms and machinery required for growth cone development and axon extension, and these have recently been targeted to stimulate robust regeneration in the injured adult central nervous system (CNS). This review summarizes recent literature highlighting a central role for organelles such as recycling endosomes, the endoplasmic reticulum, mitochondria, lysosomes, autophagosomes and the proteasome in developmental axon growth, and describes how these organelles can be targeted to promote axon regeneration after injury to the adult CNS. This review also examines the connections between these organelles in developing and regenerating axons, and finally discusses the molecular mechanisms within the axon that are required for successful axon growth.
Keywords: poranění míchy; Organelles; organelles; zvířata; Humans; regenerace nervu; Growth Cones; axon regeneration; růstové kužele; Spinal Cord Injuries; Nerve Regeneration; organely; axon growth; lidé; inter-organelle membrane contact sites; Animals